2021
DOI: 10.1002/gps.5619
|View full text |Cite
|
Sign up to set email alerts
|

Association between depressive symptoms and disability in older adults of 12 high Andean communities from Peru

Abstract: Objective: Our objective was to evaluate the association between depressive symptoms and disability in older adults residing in 12 high Andean communities in Peru. Material and Methods:We carried out a secondary data analysis of a crosssectional study that included older adults (60 years or older) from 12 high Andean communities in Peru from 2013 to 2019. Depressive symptoms were defined as a score of two or more in the abbreviated Geriatric Depression Scale, while disability was defined as a score of less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Our findings indicate the need for timely identification of cognitive frailty in primary care in order to reduce adverse outcomes. This is very important in our country due to the high prevalence of frailty (17.5 to 23.3%) and cognitive impairment (18.2 to 36.67%) described in several studies (49)(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate the need for timely identification of cognitive frailty in primary care in order to reduce adverse outcomes. This is very important in our country due to the high prevalence of frailty (17.5 to 23.3%) and cognitive impairment (18.2 to 36.67%) described in several studies (49)(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…In the Peruvian context, depression among elderly people is a signi cant public health issue. Studies conducted in the country have revealed that the prevalence of depressive symptoms in this population varies from 10.8% to 40.7% [9], [10], [11], [12], [13], [14]. This wide range of prevalence can be attributed to differences in study methodologies and the characteristics of the populations studied.…”
Section: Introductionmentioning
confidence: 94%
“…The impact of depression on elderly Peruvians is considerable. Depressive symptoms have been associated with a greater likelihood of disability in elderly individuals living at high altitudes [10]. Moreover, a positive association between depression and malnutrition has been found in this population, with a greater risk of malnutrition observed in older individuals with depression [15].…”
Section: Introductionmentioning
confidence: 99%